The effect of alternative measurement and evaluation techniques on safety performance in employee training - Dalyan, Orkun; Dalyan, Hatice; Piskin, Mehmet; Ozturk, Omer Faruk; Canpolat, Erdal (Yildiz Technical Univ, 2024)
Occupational health and safety training constitutes an important implementation step of the proactive employee welfare, health, and safety approach. In occupational health and safety training, measurement and evaluation methods should be applied accurately, efficiently, and effectively to evaluate whether learning and behavioral goals are achieved. In this research, a survey consisting of thirty questions was applied to a sample of 140 employees to determine the effect of alternative assessment tools on safety performance in occupational health and safety training. The obtained data were analyzed using the Statistical Package for Social Sciences 22 software program for reliability and exploratory factor analysis, and the Analysis of Moment Structures and Structural Equation Model 21 software program for confirmatory factor analysis, respectively. It was determined that the average score of the experimental group subjected to hazard detection poster exams using alternative assessment tools exceeded the average score of the control group taking traditional multiple-choice exams and that the level of participation in occupational health and safety regulations had a moderate positive effect on safety performance. The importance of both compulsory occupational health and safety training for primary school graduates and customized training programs for this group was emphasized. There was a positive and significant correlation between occupational health and safety compliance and safety performance. It was strongly suggested that interventions be tailored to optimum effectiveness according to training levels and that businesses also take proactive approaches to increase compliance with occupational health and safety regulations, such as organizing incentive activities and providing ongoing occupational health and safety training. A safer workplace environment should be promoted by effectively transforming the knowledge and skills acquired in occupational health and safety training into observable behaviors.
Keywords: Alternative Evaluation; Alternative Measurement; Employee Training; Safety Performance